FOOD AND BIOLOGICAL DEVELOPMENT OF SEA URCHIN TRIPNEUTES GRATILLA IN CARMEN-DANAO COVE, CEBU CENTRAL PHILIPPINES - Lamayo, Roberto C; Delan, Gloria G; Lamayo, Ma. Helian A; Bontia, Presentacion V; Juntilla, Ursina S; Camongay, Maximo L; Babaran, Monina C; Abdon, Hector C (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 1, 2015, 2015)
The sea urchin Tripneustis gratilla locally known as “swaki” has been harvested from the wild because of its gonad. The collection of the sea urchin gonads for food has been practiced for so long. However, the relationship of its biological features such as size, weight, gonadal development and sex ratio with reference to their food availability for sustainability of the species needs to be assessed. The sea urchin samples were gathered from two established sampling sites in Carmen waters, namely: Dawis Sur (Area 1) with sandy, algae and sea grass substrate and Puente (Area 2) with algae and rocky substrate. The gathered samples were analyzed in terms of its biological features. Data collected were statistically treated using correlation coefficient and t-test at 5% level of significance. There were 60 and 24 sea urchin samples collected from Area 1 and Area 2, respectively. Results show that the sea urchin from Area 1 had an average body weight of 429 g, body diameter of 4.38 cm, and gonad weight of 2.05 g, respectively. In Area 2, it has an average body weight of 139.49g, body diameter of 5.73 cm and gonad weight of 6.6, respectively. Gonadal weight and body diameter has been found to be moderately correlated in both areas (r=0.43). In terms of sex ratio, male sea urchin dominates the female in Area 2. In Area 1, there was an equal distribution of sex ratio in both sexes. Results indicates that the area with sandy, algae and seagrass substrate resulted to have heavier average body weight of sea urchin in comparison with rocky and algae substrate. Thus, food greatly influence the biological feature of sea urchin particularly its average growth rate.